ARI updates 2020 - UiTM, Accounting Research Institute (Accounting Research Institute (ARI), 2020)
Accounting Research Institute (ARI) of UiTM was first formed in 2002 as a special interest group whereas illustrate a history victorious history despite its relative youth. Since then, ARI had gone through a complete evolutionary cycle which includes of first being a special interest group (SIG), then as a research centre and finally as a research institute. The ministry of higher education formally approved the formation of ari in 2005. As a research institute, ARI is responsible to coordinate and manage the activities of its eight multi-discipline research centres (also known as units of excellence). Effective November 2009, ARI has been recognized by the ministry of higher education as one of the higher institutions' centres of excellence (HICoE).